Fire-hazard parameters of frictional sparks. Research methods. The basic problems - Ivanov, Юрий Сергеевич; Yanovskiy, С. Б. (Chrezvychaynye situatsii: obrazovanie i nauka, 2006)
The analysis of frictional spark formation of technical materials is given. The necessity of development of the legislative documentation, regulating application of materials for spark formation and the methods of experimental estimation of materials spark formation is shown.